PERSEPSI MASYARAKAT TERHADAP PENGEMBANGAN EKOWISATA DI KECAMATAN BATUKLIANG UTARA - Muh. Zaini Hasanul Muttaqin; Asrorul Azizi; Mulia Rasyidi; M. Yadi Saputra; Aswari Almahera (LPPM Institut Pendidikan Nusantara Global, 2023)
This study aims to examine the potential of ecotourism and community perceptions of developing ecotourism in North Batukliang District, Central Lombok Regency, NTB Province. To assess the potential of ecotourism is done by observation. While public perception through questionnaires and interviews. The results showed that North Batukliang District has natural and cultural potential that can be developed as an ecotourism attraction. This is also supported by public perceptions which state that the community agrees with the development of ecotourism in North Batukliang District.